Environmental impact of solid waste filler in porous asphalt mixture. (11th October 2021) - Yang, Bing; Li, Hui; Zhang, Hengji; Sun, Lijun; Harvey, John; Tian, Yu; Zhu, Yaoting; Zhang, Xiao; Han, Daqian; Liu, Liyuan
Highlights: Diatomite and bauxite residues had better raveling resistance than fly ash. The physical and chemical characteristics of the fillers affected the properties. Higher porosity and raveling loss resulted in more metal and higher pH. The coating effect of asphalt film reduced the metallic concentration and pH. Abstract: The solid wastes have been applied to asphalt pavements for many years, however, the potential environmental impact of porous asphalt mixture with solid wastes needs further research. This study chose three types of solid wastes (fly ash, diatomite and bauxite residues) and the traditional limestone as filler, the mechanical performance of porous asphalt mixtures prepared with four types of fillers was investigated with by Cantabro tests under three conditions. And the leaching characteristics of filler + aggregate, dense asphalt mixtures and porous asphalt mixtures with different raveling loss were discussed. The results of Cantabro tests indicated that diatomite and bauxite residues replacing limestone as fillers could improve the raveling resistance of porous asphalt mixtures under three types of Cantabro tests, which could be related to their larger specific surface area. The pH and metallic concentrations in the leachate of various asphalt mixtures were significantly lower than those of the corresponding filler + aggregate, which could be related to the coating of asphalt film and the adhesion between asphalt and metal pollutants. The leaching of alkalinity and various metal pollutants were related to the physical and chemical characteristics of the fillers. Larger specific surface area and more metal components could result in higher pH and metallic concentration. The leaching concentration of various metal pollutants and pH increased with the increase of raveling loss and porosity of asphalt mixture. Therefore, when the solid wastes are used in asphalt pavements, it is necessary to evaluate the long-term environmental impact of industrial solid wastes on asphalt pavements, especially porous asphalt pavements.